(untitled) (Indian Journal of Animal Production and Management, 2016)
Scientific research on factors causing the reduction in welfare of sheep and goats is rather recent and information on this topic is still scarce. Sheep and Goats, considered very rustic animals, are reared prevalently under extensive production systems and are widespread mainly in marginal areas. For these reasons, only few studies on the welfare of these species have been carried out in the past. Climatic extremes and seasonal fluctuations in herbage amount and quality are important causes of the reduction of well-being in extensive production systems, which can impair production efficiency of grazing animals and dramatically affect the welfare and health status of sheep and goats. More recently, the scenario has changed, due to a gradual diffusion of intensive and semi-intensive production systems, especially in sheep and goats to the growing concern of consumers. Research addressing animal welfare is largely focused on measurements of animal behavior, stress physiology, veterinary epidemiology, environmental physiology, environmental design, comparative psychology and studies of the behavior of animal handlers, together with conventional fields such as nutrition and microbiology16, 17, 29.